1983
DOI: 10.1016/0003-9969(83)90019-5
|View full text |Cite
|
Sign up to set email alerts
|

Secretory protein synthesis in parotid glands of young and old rats

Abstract: To determine whether the synthesis of secretory proteins changes with age, the incorporation of [14C]-leucine into exportable proteins of the parotid gland was compared in 2- and 24-month-old rats. The proteins were separated by SDS-gel electrophoresis of the post-microsomal supernatant and identified by comparing the banding patterns in gels prepared from unstimulated glands with those from the glands stimulated to secrete. The amount of radioactivity incorporated into the bands corresponding to exportable pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Age-associated decreases in the amount of c -amylase activity of rat parotid gland are accompanied by reduced levels of amino acid incorporation into total protein and, specifically, into aamylase (Kimetal., 1980;Kim, 1981;Baumetal., 1982). Amino acid incorporation into other secretary proteins is similarly reduced with age (Kim and Calkins, 1983). Restitution of secretary material by rat submandibular gland occurs more slowly following stimulation with isoproterenol in aged animals (Mysliwski, 1977).…”
Section: Discussionmentioning
confidence: 94%
“…Age-associated decreases in the amount of c -amylase activity of rat parotid gland are accompanied by reduced levels of amino acid incorporation into total protein and, specifically, into aamylase (Kimetal., 1980;Kim, 1981;Baumetal., 1982). Amino acid incorporation into other secretary proteins is similarly reduced with age (Kim and Calkins, 1983). Restitution of secretary material by rat submandibular gland occurs more slowly following stimulation with isoproterenol in aged animals (Mysliwski, 1977).…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that reductions occur in the amylase content in saliva (Meyer et al, 1937;Meyer and Necheles, 1940;Chilla et al, 1974), as well as the secretion and the rate of flow of saliva (Bertram, 1967). We have shown previously that the rate of protein synthesis declines with age in rat parotid glands 1980, Kim, 19811, and that this decline reflects the reduction in the synthesis of secretory proteins (Kim et al, 1982;Kim and Calkins, 1983). These age-related changes that affect the salivary content and the synthesis of protein suggest that alterations occur in the structural elements of the secretory acinar cells of the gland.…”
mentioning
confidence: 88%
“…Studies of the rate of synthesis of secretory proteins or their messenger RNA (mRNA) indicate that changes affecting functions of salivary glands occur during aging. It previously has been shown that rates of synthesis of proteins decline progressively with age in the rat parotid Kim, 1981Kim, , 1985Kim and Arisumi, 1985;Kim et al, 1980;Koller et al, 1992) and submandibular glands Koller et al, 1992). In the rat parotid gland, the rate of synthesis of amylase declines with age; this decline is accompanied by a parallel reduction in the level of amylase mRNA (Kim et al, 1992;Koller et al, 1992).…”
Section: Protein Synthesismentioning
confidence: 99%